SRG/eROSITA uncovers the most X-ray luminous quasar at z > 6. Issue 2 (4th August 2020) - Medvedev, P; Sazonov, S; Gilfanov, M; Burenin, R; Khorunzhev, G; Meshcheryakov, A; Sunyaev, R; Bikmaev, I; Irtuganov, E
ABSTRACT: We report the discovery of X-ray emission from CFHQS J142952+544717, the most distant known radio-loud quasar at z = 6.18, on 2019 December 10–11 with the eROSITA telescope on board the SRG satellite during its ongoing all-sky survey. The object was identified by cross-matching an intermediate SRG / eROSITA source catalogue with the Pan-STARRS1 distant quasar sample at 5.6 < z < 6.7. The measured flux ∼8 × 10 −14 erg cm −2 s −1 in the 0.3–2 keV energy band corresponds to an X-ray luminosity of 2.6^+1.7_-1.0× 10^46 erg s −1 in the 2–10 keV rest-frame energy band, which renders CFHQS J142952+544717 the most X-ray luminous quasar ever observed at z > 6. Combining our X-ray measurements with archival and new photometric measurements in other wavebands (radio to optical), we estimate the bolometric luminosity of this quasar at ∼(2–3) × 10 47 erg s −1 . Assuming Eddington limited accretion and isotropic emission, we infer a lower limit on the mass of the supermassive black hole of ∼2 × 10 9 M⊙ . The most salient feature of CFHQS J142952+544717 is its X-ray brightness relative to the optical/UV emission. We argue that it may be linked to its radio-loudness (although the object is not a blazar according to its radio properties), specifically to a contribution of inverse Compton scattering of cosmic microwave background photons off relativistic electrons in the jets. If so, CFHQS J142952+544717 might be the tip of the iceberg of high- z quasars with enhanced X-ray emission, and SRG / eROSITA may find many more such objects during its 4-yr all-sky survey.